2020
DOI: 10.1109/access.2020.2967747
|View full text |Cite
|
Sign up to set email alerts
|

Small Cells Enabled by Crowdsourced Radio Units Mounted on Parked Vehicles for Smart City

Abstract: A large number of small cells are densely deployed in the era of 5G and beyond 5G mobile networks to achieve high rate and low latency data transmission. Small cells are composed with fixed ground radio units (RUs) in the conventional networks, and thus the utilization rate of them is drastically deteriorated due to the spatio-temporal patterns of mobile traffic demand. To address this problem, adaptive network architectures have been investigated to reconfigure networks on demand using small cells mounted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…On the other hand, the throughput increased roughly from 200 Mbps (for static macro and small cell deployments) to a maximum of 700 Mbps with the installation of antennas on vehicles parked in office parking lots. Similarly, in [109], the authors found a strong correlation between cellular traffic demand and occupancy rate of neighboring parking lots similar to [108]. The authors proposed to install cells on the vehicles that are frequently parked in parking lots (near offices or shopping plazas etc.…”
Section: A Performance Enhancement With Moving Networkmentioning
confidence: 66%
See 3 more Smart Citations
“…On the other hand, the throughput increased roughly from 200 Mbps (for static macro and small cell deployments) to a maximum of 700 Mbps with the installation of antennas on vehicles parked in office parking lots. Similarly, in [109], the authors found a strong correlation between cellular traffic demand and occupancy rate of neighboring parking lots similar to [108]. The authors proposed to install cells on the vehicles that are frequently parked in parking lots (near offices or shopping plazas etc.…”
Section: A Performance Enhancement With Moving Networkmentioning
confidence: 66%
“…Mobile operators feel reluctant to make investments in infrastructure where the return on investment is low (as in the above-mentioned scenario). The non-static nature of moving networks makes them an ideal and cost effective alternative as compared to fixed small cell infrastructure as discussed in [23], [52], [68], [108], [109].…”
Section: A Performance Enhancement With Moving Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…New radio techniques are being explored in 5G cellular systems. One of the main lines of research in this field focuses on the use of small 5G cells, the deployment of massive antenna techniques and the use of 'COMP' coordination techniques between cells [2].…”
Section: Introductionmentioning
confidence: 99%